Biernat, Carolina (2024). Ciudadanía enferma: Las venéreas en Argentina, 1900-1960. Buenos Aires: Editorial Biblos, 199 páginas - Martínez, María Emilia (2025)
Reseña del Libro Ciudadanía enferma: Las venéras en Argentina, 1900-1960 por C. Biernat